Review of the new production models: Circular Economy, Bioeconomy and Biosociety (Research, Society and Development, 2021)
Population increase and the conventional form of linear production make it necessary to analyze concepts related to circular economy, bioeconomy and biosociety, theories that already exist and that are already applicable in many sectors of society. In this sense, the concern with the quality of life and of the environment are precursors for the development of a society with a greater commitment to new, cleaner and more optimized modes of production. Therefore, this article brings a review on the new production models, involving the circular economy, bioeconomy and biosociety. Its objective is introducing the concept as a sustainable technological alternative, which makes processes cleaner and more economical, such as the optimization of processes and the use of biomass and other wastes. The research was developed by building a review on the topic, then going through a general approach, presenting the origin, applicability and technological characteristics of the topic. It concludes, with emphasis, the importance of studying new production models to promote and improve the capacity for cleaner and more sustainable production, in addition to enhancing the dissemination of these concepts through research.